Keanekaragaman Spesies Kupu-kupu di Gunung Jae Kabupaten Lombok Barat sebagai Materi Pengayaan Pelajaran Biologi SMA - Ulpa, Maria; Ilhamdi, Mohammad Liwa; Hadiprayitno, Gito (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Butterflies have important values for humans and the environment, such as ecological, aesthetic, educational, conservation, and cultural values. Mount Jae is a butterfly habitat located in Sedau Village, Narmada District, West Lombok Regency. This exploratory descriptive study aims to determine the diversity of butterfly species in Gunung Jae, West Lombok Regency as enrichment material for high school biology lessons. This research was conducted from March to April 2023. Data was collected using a survey method with a sweeping net technique and following two predetermined observation paths, namely the path of the lake by the rice fields and the path of the lake by the dam. In this study, the number of butterflies that were found was 381 individuals consisting of 22 species, 18 genera, and 5 families (Papilionidae, Nymphalidae, Pieridae, Lycaenidae, and Hesperiidae). The highest relative abundance found was from the Nymphalidae family (54.3%) and the lowest relative abundance was from the Papilionidae family (7.6%). Analysis of the species diversity index of butterflies used the Shannon-Wienner formula and obtained a species diversity index (H’) value for all species of 2.946. The results of the validation show that booklets are very good for use as enrichment material in the learning process, with the percentage of media experts 98.1% and material experts 97.7% with a very valid validity category.